Dead wake : the last crossing of the Lusitania - Larson, Erik, 1954- (New York : Crown Publishers, an imprint of the Crown Publishing Group, a division of Random House LLC, a Penguin Random House Company, 2015)
A 100th-anniversary chronicle of the sinking of the Lusitania that discusses the factors that led to the tragedy and the contributions of such figures as President Wilson, bookseller Charles Lauriat and architect Theodate Pope Riddle.
Mining suspense -- A word from the captain -- "Bloody monkeys" -- Jump rope and caviar -- Dead wake -- The black soul -- The sea of secrets -- Epilogue: personal effects.
Map on lining papers.
Includes bibliographical references (pages 411-418) and index.
Keywords: Lusitania (Steamship).; World War, 1914-1918 -- Naval operations, German; Shipping -- Government policy -- Great Britain -- History -- 20th century